Lorcaserin Inhibit Glucose-Stimulated Insulin Secretion and Calcium Influx in Murine Pancreatic Islets - Muhan Jing; Shanshan Wang; Ding Li; Zeyu Wang; Ziwen Li; Yichen Lu; Tong Sun; Tong Sun; Chen Qiu; Fang Chen; Fang Chen; Haijuan Yu; et al. (Frontiers Media S.A., 2021)
Lorcaserin is a serotonergic agonist specific to the 5-hydroxytryptamine 2c receptor (5-HT2CR) that is FDA approved for the long-term management of obesity with or without at least one weight-related comorbidity. Lorcaserin can restrain patients' appetite and improve insulin sensitivity and hyperinsulinemia mainly through activating 5-HT2CR in the hypothalamus. It is known that the mCPP, a kind of 5-HT2CR agonist, decreases plasma insulin concentration in mice and previous research in our laboratory found that mCPP inhibited glucose-stimulated insulin secretion (GSIS) by activating 5-HT2CR on the β cells. However, the effect of lorcaserin on GSIS of pancreatic β cell has not been studied so far. The present study found that 5-HT2CR was expressed in both mouse pancreatic β cells and β-cell-derived MIN6 cells. Dose-dependent activation of 5-HT2CR by lorcaserin suppressed GSIS and SB242084 or knockdown of 5-HT2CR abolished lorcaserin's effect in vitro. Additionally, lorcaserin also suppressed GSIS in high-fat diet (HFD)-fed mice in dose-dependent manner. Lorcaserin did not change insulin synthesis ATP content, but lorcaserin decrease cytosolic free calcium level [(Ca2+)i] in MIN6 cells stimulated with glucose and also inhibit insulin secretion and (Ca2+)i in MIN6 treated with potassium chloride. Furthermore, stimulation with the L-type channel agonist, Bay K8644 did not restore GSIS in MIN6 exposed to lorcaserin. Lorcaserin inhibits the cAMP generation of MIN6 cells and pretreatment with the Gα i/o inhibitor pertussis toxin (PTX), abolished lorcaserin-induced suppression of GSIS in β cells, while membrane-permeable cAMP analogue db-cAMP had same effect as PTX. These date indicated lorcaserin coupled to PTX-sensitive Gα i/o proteins in β cells reduced intracellular cAMP level and Ca2+ influx, thereby causing GSIS dysfunction of β cell. These results highlight a novel signaling mechanism of lorcaserin and provide valuable insights into the further investigation of 5-HT2CR functions in β-cell biology and it also provides guidance for the clinical application of lorcaserin.